2020
DOI: 10.1002/fsn3.1426
|View full text |Cite
|
Sign up to set email alerts
|

Safety assessment of glutaminase from Aspergillus niger

Abstract: Glutaminase (glutamine aminohydrolase EC 3.5.1.2) is used in the production of food ingredients rich in l‐glutamic acid that are added to finished foods for the purpose of enhancing or improving the savory flavor profile of food. The glutaminase enzyme preparation evaluated in these studies, designated as Sumizyme GT hereafter, is obtained by fermentation of Aspergillus niger strain GT147. The safety of Sumizyme GT was evaluated in a series of standard toxicological studies, including a 90‐day oral toxicity st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The "treat-and-wash" method was employed in bacterial reverse mutation tests on other enzymes intended for food production which support the conclusion of a non-mutagenicity of purine nucleosidase under the conditions of this assay. [32][33][34] The lack of genotoxic potential of purine nucleosidase from A. luchuensis was further confirmed in the in vitro mammalian chromosome aberration assay in which no evidence of clastogenic effects were observed up to the highest concentrations tested.…”
Section: Discussionmentioning
confidence: 77%
“…The "treat-and-wash" method was employed in bacterial reverse mutation tests on other enzymes intended for food production which support the conclusion of a non-mutagenicity of purine nucleosidase under the conditions of this assay. [32][33][34] The lack of genotoxic potential of purine nucleosidase from A. luchuensis was further confirmed in the in vitro mammalian chromosome aberration assay in which no evidence of clastogenic effects were observed up to the highest concentrations tested.…”
Section: Discussionmentioning
confidence: 77%
“…Given that the material is largely proteinaceous, this finding is not surprising and is consistent with the studies of other enzymes produced from other microorganisms, including Aspergillus oryzae and A. niger. 37,38 While the current data support the safety of the β-fructofuranosidase enzyme concentrate produced from A. brunneoviolaceus, it is typical that the safety assessment of enzyme products give consideration to the source organism in addition to the inherent hazard profile of the enzyme. 27,39 No published scientific opinions regarding the safety of A. brunneoviolaceus were identified.…”
Section: Discussionmentioning
confidence: 92%
“…Most microbial L-asparaginases have glutaminase activity, which may cause clinical side effects regarding the use of L-asparaginase as a therapeutic agent. Glutaminase, catalyzing the hydrolytic deamination of L-glutamine to yield L-glutamate and ammonia, has an indirect role in imparting or enhancing the flavor profile of foods by increasing the L-glutamate content of intermediate food ingredients [ 128 ]. Claeys et al reported that the addition of glutamine had a strong promoting effect on acrylamide formation [ 129 ].…”
Section: Discussionmentioning
confidence: 99%